A Deixis Analysis in Song Lyrics of Anti-Hero by Taylor Swift - Lailiyah, Manda Ayu; Aisyah, Siti; Prasetyo, Yudy (Journal of English Language and Education, 2026)
Deixis is an important pragmatic feature in song lyrics because it enables listeners to interpret meaning based on context, perspective, and interpersonal relations between the songwriter and the audience. In linguistic and pragmatic studies, deixis plays a crucial role in constructing narrative voice, emotional expression, and contextual interpretation. Although previous studies have analyzed deixis in various song lyrics, limited attention has been given to how different types of deixis contribute to the expression of internal conflict, identity struggle, and self-reflection in Taylor Swift’s “Anti-Hero”. Therefore, this study aims to identify the types of deixis found in the song lyrics Anti Hero by Taylor Swift and to describe the contextual meaning of those deixis. This research employed a descriptive qualitative method using a pragmatic approach based on Levinson’s (1983) deixis framework. The data source was the official song lyrics obtained from the Genius website and analyzed through systematic identification, classification, and contextual interpretation using an analytical rubric. The findings reveal that the lyrics contain several types of deixis, namely person, temporal, spatial, discourse, and social deixis, each contributing to the construction of meaning within the song. The study concludes that deixis in “Anti-Hero” functions not merely as a grammatical referencing system but as a pragmatic resource that shapes contextual meaning, emotional expression, and self-reflective narrative, allowing listeners to engage with the songwriter’s personal perspective.